1993
DOI: 10.1103/physrevb.47.15097
|View full text |Cite
|
Sign up to set email alerts
|

Collective excitations in liquid deuterium: Neutron-scattering and correlated-density-matrix results

Abstract: The collective dynamics of liquid deuterium is studied by means of inelastic neutron scattering (INS) at 20.14 K and under 2 bars of applied pressure using two different incident energies. The low-incident-energy (high-energy-resolution) spectra are studied in detail by means of a time-of-flight (TOF) technique, whereas the finite-frequency response is investigated using a higher incident energy on a triple-axis spectrometer (TAS). The main finding of our work is the observation by the latter experimental tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 35 publications
3
19
0
Order By: Relevance
“…In liquid hydrogens, the diffusive motion at small κ is well described [16] by the Langevin equation…”
Section: Methods Of Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…In liquid hydrogens, the diffusive motion at small κ is well described [16] by the Langevin equation…”
Section: Methods Of Calculationmentioning
confidence: 99%
“…Since the neutron experiments revealed that ∆ diff is almost constant at higher momentum transfers, we fix its value at κ > κ max . For example, κ max ≈ 1.7Å −1 in the case of 20-K liquid deuterium [16]. The collective-motion contribution S pho to S i can be described using the following incoherent phonon expansion for a harmonic crystal [14,24]:…”
Section: Methods Of Calculationmentioning
confidence: 99%
“…Collective excitations in liquid helium constitute a well-established research field, which would deserve by itself a wholly dedicated treatment [8,9]. Hydrogen and deuterium have also been the subject of several investigations [10][11][12][13][14][15][16][17]. Their molecular nature is not an obstacle due to the separability of the centre-of-mass translational dynamics from the rotovibrational motions [18].…”
Section: Introductionmentioning
confidence: 99%
“…16 We have studied both single particle as well as collective fluctuations, with good agreement with recent experiments performed on liquid para-hydrogen 19,20,21,22,23 and liquid ortho-deuterium. 24,25,26 Unlike the MaxEnt technique, our approach is a theory and thus provides additional insight into the dynamics of quantum liquids. This fact implies several additional advantages.…”
Section: Introductionmentioning
confidence: 99%